What Does Digital Journalism Studies Look Like?. Issue 3 (16th March 2019) - Steensen, Steen; Grøndahl Larsen, Anna M.; Hågvar, Yngve Benestad; Fonn, Birgitte Kjos
Abstract: This article analyses the characteristics of digital journalism studies through an empirical investigation of all articles published in the journal Digital Journalism, from its launch in 2013 to issue 6, 2018. The aim of the analysis is to identify dominant themes and degrees of diversity and interdisciplinary in digital journalism studies, and to identify biases and blind spots. The article is based on analysis of keywords, abstracts and references used in all articles published in the journal. The findings suggest that while the research published in Digital Journalism is firmly situated within journalism studies, it has a stronger emphasis on technology, platforms, audience and the present. The article also finds that digital journalism studies, as seen in Digital Journalism, is dominated by perspectives from the social sciences, while largely ignoring digital journalism as a meaning-making system, and that the field of research could benefit from the application of theories and perspectives from the humanities and to some extent from theoretical computer science and informatics. Finally, the article argues that digital journalism studies suffers from a lack of connections between empirical research and the many conceptual discussions that dominate the (sub)field.